EFFECT OF PLANT GEOMETRIES ON YIELD AND QUALITY COMPONENTS OF QUINOA LEAVES (Chenopodium quinoa) UNDER SOUTHERN TELANGANA - and W. JESSIE SUNEETHA, K. ARPITHA REDDY, B. NEERAJA PRABHAKAR (The Journal of Research, PJTSAU, 2021)
Quinoa (Chenopodium quinoa Willd.) belongsÂ to the group of crops known as pseudo cerealsÂ (Cusack, 1984; Kozoil, 1993) and to theÂ Amaranthaceae family Quinoa is one of the oldestÂ crops in the Andean region, with approximately 7000Â years of cultivation, and great cultures such as theÂ Incas and Tiahuanaco have participated in itsÂ domestication and conservation (Jacobsen, 2003).Â Quinoa was first botanically described in 1778 as aÂ species native to South America, whose center ofÂ origin is in the Andean of Bolivia and Peru. Recently,Â it has been introduced in Europe, North America, AsiaÂ and Africa (FAO, 2011). The year 2013 has beenÂ declared â€œThe International Year of the Quinoaâ€ (IYQ)Â by the United Nations. This crop is a natural foodÂ resource with high nutritive value and is becoming aÂ high quality food for health and food security, forÂ present and future human generations.